MANAGING ISLAMIC PUBLIC SPACE: Responses of Sumantran Malay Muslims toward “Neo-anti Bid’ah Movement” (State Islamic University (UIN) of Sunan Ampel Surabaya, 2013)
It has been argued by scholars that Indonesia can be a model of religious tolerance to the Muslim world. However, while a dramatic increase of intolerant acts against minorities in 2009-2012 across the country have challenged this argument, how the majority, to some extent, have also suffered due to similar actions by those who are not really representing the majority and how they respond to it has been almost completely ignored by all for a very long time. Cases in which Sumatran ‘traditionalist’ Malay Muslims have to abandon their own mosques in order to avoid disharmony potentials among themselves are significant examples. In this paper I present a valuable harmonious life in Jambi Malay Muslim community despite so many actions that can lead to conflicts. However, I also consider and contextualize the long-run implications of these responses, particularly regarding Muslim’s contenstation of Islamic public space and the problem of maintenance of a healthy democratic society.